Analysis of Media Use and Learning Interaction to Improving Student Engagement - Yulhendri, Yulhendri; Mardhotillah, Nurul Izzah; Alisha, Wyanet Putri; Susanti, Nora (Fakultas Ekonomi, Universitas Negeri Semarang, 2022)
This research aimed to test the effect of multimedia and lecturer-student interaction on student engagement in students of the Faculty of Economics, Universitas Negeri Padang. This type of research was descriptive quantitative. The sample was taken by using the Slovin formula with 358 respondents. The measure used in the study was the likert scale. The type of data used in this study was primary data obtained through the dissemination of questionnaires to students of the Faculty of Economics, Universitas Negeri Padang. The analysis method used SEM PLS analysis using SmartPLS 3.0. The results of this study showed that: lecturer-student interaction had a significant effect on student engagement. Multimedia had a significant effect on lecturer-student interaction. Multimedia had no significant effect on student engagement. The implication of this study was that empirically in learning that online student interaction was very necessary in order to increase student involvement in learning. Then, the use of multimedia affected student involvement in learning. The future research agenda needs to study more deeply the use of multimedia on student involvement in learning.